Understanding the retail customer - Banks, Jonathan (Henry Stewart Talks, 2009)
What are consumers concerned with and how does that impact their grocery purchasing?, Four megatrends, Retail trends, Grocery store differentiators and the drivers of store equity, Discussion of the importance of price, private label and the rise of the discounters